A discourse analysis of teachers' messages in official and unofficial WhatsApp groups - Hussein, Suzan Farouq F.; Rashid, Radzuwan Ab; Azizan, Mazlin; Alali, Omar Mohammad Mousa (Frontiers in Communication, 2023)
This study explores Jordanian English language teachers' social and discursive practices online. It aims to scrutinize the way Jordanian English language teachers at one of universities in Jordan construct their posts in official and unofficial WhatsApp groups. Employing an ethnographic approach, this paper examines the differences in teachers' discursive behavior in official and unofficial WhatsApp groups. Data generation took place from March 2018 to May 2018. The data were obtained from participants' observation in both official and unofficial WhatsApp groups. 18 English language teachers participated in this study. A total of 817 posts were made throughout the observation period which were included in the analysis. Data generated through participant observations were analyzed using discourse analysis combined with discursive psychology approach. The findings suggest that teachers behave differently in how they talk to their superiors than in how they speak to their colleagues to construct their desired identities. They convey a positive impression to their leaders, and they tend to use persuasive techniques to appear more friendly to others. Exemplification, ingratiation and self-promotion were the impression management techniques used by the participants. This paper concludes that Jordanian English language teachers convey a positive impression to their superiors as they do not want to jeopardize their careers.